From Stress To Success: A Systematic Review of Integrative Psychoeducational Interventions for College Student Success - Nadia Aulia Nadhirah; Muhammad Solehuddin; Popy Mayasari Afendy; Ilfiandra Ilfiandra (Universitas Negeri Semarang, 2025)
This study demonstrates that targeted psychoeducational interventions significantly reduce academic stress and enhance well-being among college students. Using the Systematic Literature Review (SLR) method and the PRISMA 2020 protocol, the research evaluates the outcomes and mechanisms of these interventions on students' academic flourishing. Analysis of ten recent empirical articles from 2015 to 2024, sourced from Scopus, Web of Science, PubMed, and Google Scholar, underpins the findings. Thematic analysis reveals that Cognitive Behavioral Therapy (CBT)-based psychoeducation is effective at lowering stress symptoms, while PERMA model-based interventions foster resilience and enduring psychological development. Interventions lasting 5 to 8 weeks are most effective at driving sustained behavioral change. Crucially, digitizing services and adopting multimodal approaches further increase accessibility and destigmatize mental health support. The evidence supports integrating holistic psychoeducational programs into higher education to build supportive academic environments that promote student success.